Molecular cloning and sequencing of the cDNA and gene for a novel elastinolytic metalloproteinase from Aspergillus fumigatus and its expression in Escherichia coli. - Sirakova, T D (1994)
An extracellular elastinolytic metalloproteinase, purified from Aspergillus fumigatus isolated from an aspergillosis and patient/and an internal peptide derived from it were subjected to N-terminal sequencing. Oligonucleotide primers based on these sequences were used to PCR amplify a segment of the metalloproteinase cDNA, which was used as a probe to isolate the cDNA and gene for this enzyme. The gene sequence matched exactly with the cDNA sequence except for the four introns that interrupted the open reading frame. According to the deduced amino acid sequence, the metalloproteinase has a signal sequence and 227 additional amino acids preceding the sequence for the mature protein of 389 amino acids with a calculated molecular mass of 42 kDa, which is close to the size of the purified mature fungal proteinase. This sequence contains segments that matched both the N terminus of the mature protein and the internal peptide. A. fumigatus metalloproteinase contains some of the conserved zinc-binding and active-site motifs characteristic of metalloproteinases but shows no overall homology with known metalloproteinases. The cDNA of the mature protein when introduced into Escherichia coli directed the expression of a protein with a size, N-terminal sequence, and immunological cross-reactivity identical to those of the native fungal enzyme. Although the enzyme in the inclusion bodies could not be renatured, expression at 30 degrees C yielded soluble enzyme that showed chromatographic behavior identical to that of the native fungal enzyme and catalyzed hydrolysis of elastin. The metalloproteinase gene described here was not found in Aspergillus flavus.